PENERAPAN TEKNIK PENANGKARAN PENGEMBANGBIAKAN LABI-LABI (Amyda cartilaginea) DI AREA PT. ARARA ABADI - Fanny Kusuma Akmal; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Trionychia (Amyda cartilaginea) or better known as the machinations (bulus) by the public is one of the endangered species its conservation. Breeding is one way to support the conservation efforts of these animals and their germplasm. Breeding activity is done to maintain endangered animals like trionychia. This study aims to identify the breeding technique of Trionychia at PT. Arara Abadi and to compare it with existed literature about trionychia. The Methods of data collection are observation, interview and literature study. The data have been obtained by observation and interview that are conducted during the study compiled into the form of a table based on the type of activities that can be taken to a conclusion. The research finding showed that the breeding thechnique of trionychia at PT. Arara Abadi is included to ex situ breeding and based on the comparison between the data on the field and its literature, it is included to intensive breeding. Keyword: Amyda cartilaginea, Breeding, PT. Arara Abadi.